2018
DOI: 10.1021/acscatal.8b00140
|View full text |Cite
|
Sign up to set email alerts
|

Surface Alloy Composition Controlled O2 Activation on Pd–Au Bimetallic Model Catalysts

Abstract: Oxygen is an important reactant in several catalytic conversions and partial oxidation reactions on Pd–Au alloy surfaces; however, adsorption and dissociation are not fully understood, especially as a function of the surface alloy composition. In this study, we probe the influence of the atomic makeup of the surface of Pd–Au catalysts regarding control of the catalytic activity toward O2 dissociation and the reactivity of the resulting oxygen adatoms. To experimentally investigate this, we prepared various bim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 68 publications
(164 reference statements)
6
82
0
Order By: Relevance
“…[124,125] This is in good agreement with the work of Han and Mullins who have recently probed the influnce of the surface composition of AuÀ Pd catalysts for OÀ O bond dissociation, widely believed to be a key step for the formation of H 2 O, and have reported that the extent of O 2 dissociaton is proportional to Pd content, with the increasing development of Pd ensembles attributed as the cause for increased OÀ O bond cleavage and a resulting increase in H 2 O formation. [126] A further study by Li and Yoshizawa [127] into the role of Au in bi-metallic AuPd systems has suggested a more direct involvement of Au in the production of H 2 O 2 ( Figure 5). They calculated the energetic favourability of OÀ O bond cleavage that exists over a pure Pd surface is reduced through the introduction of Au, to a state where the maintenance of the OÀ O bond is favoured, resulting in the high selectivity of AuPd systems reported experimentally in the literature.…”
Section: Synthesis Of H 2 Omentioning
confidence: 95%
See 1 more Smart Citation
“…[124,125] This is in good agreement with the work of Han and Mullins who have recently probed the influnce of the surface composition of AuÀ Pd catalysts for OÀ O bond dissociation, widely believed to be a key step for the formation of H 2 O, and have reported that the extent of O 2 dissociaton is proportional to Pd content, with the increasing development of Pd ensembles attributed as the cause for increased OÀ O bond cleavage and a resulting increase in H 2 O formation. [126] A further study by Li and Yoshizawa [127] into the role of Au in bi-metallic AuPd systems has suggested a more direct involvement of Au in the production of H 2 O 2 ( Figure 5). They calculated the energetic favourability of OÀ O bond cleavage that exists over a pure Pd surface is reduced through the introduction of Au, to a state where the maintenance of the OÀ O bond is favoured, resulting in the high selectivity of AuPd systems reported experimentally in the literature.…”
Section: Synthesis Of H 2 Omentioning
confidence: 95%
“…A number of theoretical studies by Yoshizawa and co‐workers compared Pd and PdAu surfaces and provided evidence that the presence of Au inhibits the formation of H 2 O, compared to that over a Pd (111) surface ,. This is in good agreement with the work of Han and Mullins who have recently probed the influnce of the surface composition of Au−Pd catalysts for O−O bond dissociation, widely believed to be a key step for the formation of H 2 O, and have reported that the extent of O 2 dissociaton is proportional to Pd content, with the increasing development of Pd ensembles attributed as the cause for increased O−O bond cleavage and a resulting increase in H 2 O formation . A further study by Li and Yoshizawa into the role of Au in bi‐metallic AuPd systems has suggested a more direct involvement of Au in the production of H 2 O 2 (Figure ).…”
Section: The Role Of Secondary Metals In the Direct Synthesis Of H2o2mentioning
confidence: 99%
“…The synergistic effect of the AuPd bimetallic surface for the O 2 activation compared with the Au surface alone has been well documented . Han and Mullins and Li and co‐workers reported that the propensity of O 2 adsorption is correlated with the coverage of isolated Pd active sites by Au atoms. If isolated Pd sites surrounded by Au are neighbored, O 2 activation is promoted.…”
Section: Resultsmentioning
confidence: 99%
“…The main driving force in the formation of the surface alloy is the relaxation of the strain energy between adjacent atoms near the surface . As a thermodynamically stable, ultrathin mixture of atoms confined at a surface or interface, surface alloys have been used to provide a unique environment for studying surface physics and chemistry, and are now expected to be suitable reservoirs of precursors for the growth of various 2 D nanomaterials, including graphene and transition metal dichalcogenides …”
Section: Introductionmentioning
confidence: 99%
“…[16] The main drivingf orce in the formationof the surface alloy is the relaxationof the strain energy betweena djacent atomsn ear the surface. [16,17] As a thermodynamically stable, ultrathin mixture of atomsc onfined at as urface or interface, [13] surface alloys have been used to provide au nique environmentf or studyings urfacep hysics and chemistry, [18][19][20][21] and are now expected to be suitable reservoirs of precursors for the growth of various 2D nanomaterials, including graphene and transitionm etal dichalcogenides. [2,4,[22][23][24][25] However,i nt he following year,K ang et al [5] reported an ew method of MOCVD, which uses Mo(CO) 6 and (C 2 H 5 ) 2 S( diethyl sulfide, Et 2 S) to yield 2D MoS 2 directlyo na rbitrary substrates at 550 8Ca fter reaction for 26 h. Despite the different reaction conditions of the MOCVD and the Au-assisted CVD, the potential capability of the precursors to synthesize MoS 2 withouta ny catalystss uggested that the formation of as urface alloy may not have occurred during the Au-assisted CVD.…”
Section: Introductionmentioning
confidence: 99%